Rhizosphere Microbiomes of European Seagrasses Are Selected by the Plant, But Are Not Species Specific - Cúcio, Catarina; Engelen, Aschwin H.; Costa, Rodrigo; Muyzer, Gerard (Frontiers in Microbiology, 2016)
Seagrasses are marine flowering plants growing in soft-body sediments of intertidal and shallow sub-tidal zones. They play an important role in coastal ecosystems by stabilizing sediments, providing food and shelter for animals, and recycling nutrients. Like other plants, seagrasses live intimately with both beneficial and unfavourable microorganisms. Although much is known about the microbiomes of terrestrial plants, little is known about the microbiomes of seagrasses. Here we present the results of a detailed study on the rhizosphere microbiome of seagrass species across the North-eastern Atlantic Ocean: Zostera marina, Zostera noltii and Cymodocea nodosa. High-resolution amplicon sequencing of 16S rRNA genes showed that the rhizobiomes were significantly different from the bacterial communities of surrounding bulk sediment and seawater. Although we found no significant differences between the rhizobiomes of different seagrass species within the same region, those of seagrasses in different geographical locations differed strongly. These results strongly suggest that the seagrass rhizobiomes are shaped by plant metabolism, but not coevolved with their host. The core rhizobiome of seagrasses includes mostly bacteria involved in the sulfur cycle, thereby highlighting the importance of sulfur-related processes in seagrass ecosystems.